(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The article examines Uzbek folk crafts and their development in the system of continuous education, teaching crafts to young people. For this purpose, information is provided on the importance of the development of folk crafts as social protection, its main directions, the benefits provided by the state to artisans. Also, recommendations were given for improvement on the topic of "National embroidery" in higher educational institutions. The advantages of using the Murund method when teaching the selected topic are shown.